Effects of high dietary threonine supplementation on growth performance, health biomarkers, and intestinal histology in cyclic heat-stressed broilers - Abia Khalid; Sania Bashir; Asma Kalsoom; Hafiz Faseeh Ur Rehman; Muhammad Afzal Rashid; Mansur Abdullah Sandhu; Habib Ur Rehman; Muhammad Shahbaz Yousaf (Veterinary World)
Background and Aim: Heat stress (HS) negatively impacts poultry production by reducing growth performance and compromising physiological health. Nutritional strategies, particularly amino acid supplementation, are explored to mitigate these adverse effects. This study evaluates the impact of high dietary threonine supplementation on growth performance, health biomarkers, oxidative status, meat quality, and intestinal histology in cyclic HS broilers.